Awareness and perception on agriculture fresh produce traceability among producers and wholesalers in Malaysia - Saipul Jannah, Juliana Ritonga (2016)
Agriculture is the third engine of economic growth in Malaysia. Agriculture has been taken seriously by the Malaysian government as they made a National Agriculture Policy and follow by Agro-Food Policy and food safety is one of the eighth (8th) main ideas to perform the Agro-Food Policy. The government emphasized in safety food product especially fresh fruits and vegetables for higher and better quality and to meet the food safety standards, thus allowing access to premium markets in the Middle East and Europe. The traceability can be one of the methods that could trace products from produced stage until market. In order to implement the traceability among the product and wholesaler in Malaysia, the respective department or agencies need to know the level of awareness and knowledge among the implementers. Awareness and knowledge are required for the implementer to make a judgment whether the traceability will be benefited to them and it will result the behaviour. In many agencies, it is still to gather information and strengthen the concept of practicality. However, the responsible department and agencies are working for the implementing food chain traceability in the sector of agriculture. Therefore, this study was conducted to identify the awareness and knowledge of producers and wholesalers in traceability of fresh products. The specific objectives for this study were to describe selected demographic characteristic of the producers and wholesaler, to identify the level of awareness and knowledge of producer and wholesaler in food safety, food supply chain and traceability, to clarify the relationship between socio demographic factors with level of awareness and knowledge of traceability and to examine the factors that influences the producers and wholesalers for accepting concept of traceability. This study was used the Theory of Applied Behaviour and behaviour of human contributors in relation to the behavioural intention. A total of 200 respondent among selected farmers and wholesalers (involve in fresh product) were selected to obtain their opinions towards traceability in fresh fruits and vegetables. The quantitative method was used in this study that was involved for numerical data in which survey method through face to face interview using structure questionnaire. This study was conducted in to two states which were Johor and Pahang for producers and Selangor for wholesale. In this study, descriptive analysis, Chi-Square, factor analysis methods were applied. From the descriptive analysis, majority of the fresh producers were male with the age between 41 to 50 years old. Most of them were having secondary school. Their annual income was less than RM 100, 000 and has been involved in the farming for about 1 to 10 years. However, for the fresh wholesalers, majority of them were male at the age between 41 to 50 years old and were have secondary school education. In addition, majority of the respondents have annual income less than RM100, 000. Most of them have 21 to 30 years of experience in conducting a business. The producer and wholesaler mostly were involved as an individual. They also produced and market more in vegetables as compared to fruits. Market area for producer in district and state contributed more than 50% of their marketing strategy. However, for the wholesaler, their marketing area was around Peninsular Malaysia which was contributed more than 50% of their marketing area. In the aspect traceability on their product, only 15% of producer put batch number on their packaging and only 1% have a bar code on their packaging. Moreover, only 27%of the wholesalers put a batch number on their packaging and none of them had bar code on their packaging. It shows that, the availability of tracing their products was very low. Based from the results, the level of awareness and knowledge for food safety and supply chain was high for each group of respondents. It means that the producers and wholesalers know the importance in producing a safe vegetables and fruits for the consumers and they took the responsibilities for producing safe foods. They also know well about supply chain throughout the process, start with food production in farm level until the distribution to the consumer. However the level of awareness and knowledge towards traceability among producer and wholesaler was moderate. It shows that the available information about traceability was low and the government agencies were not taking serious part about tracing back and forward of each product which is available in the market. The Chi-square analysis results showed that in producers’ perspectives, income and education level have significant relationships with the producers’ intentions to accept the traceability on fresh produce. From the wholesalers’ perspective, the result suggests that income in business have significant different relationship with intentions of traceability acceptance. The factor analysis was extracted the factors that influence in attention of traceability producers’ perspectives, six (6) factors were extracted namely “business profile”, “market channel”, “financial”, “reputation”, “policy” and “infrastructure”. On the wholesalers’ perspectives, five (5) factors were extracted which are “financial”, “business profile”, ‘reputation’, ‘market channel’ and “infrastructure”. All of these factors were identified as it can create implementation intention amongst producers and wholesalers to perform implementation behaviour towards the traceability. Future research is recommended to conduct study on every stakeholder in supply chain including retailers, exporters and transporters in order to know their attitude, perception, knowledge and awareness of traceability practices on fresh produce so that they can comply with international standards and market requirements.